Comprehensive behavioral phenotyping of a new Semaphorin 3 F mutant mouse. Issue 1 (December 2016) - Matsuda, Ikuo; Shoji, Hirotaka; Yamasaki, Nobuyuki; Miyakawa, Tsuyoshi; Aiba, Atsu
Abstract Background Semaphorin 3 F (Sema3F) is a secreted type of the Semaphorin family of axon guidance molecules. Sema3F and its receptor neuropilin-2 (Npn-2) are expressed in a mutually exclusive manner in the embryonic mouse brain regions including olfactory bulb, hippocampus, and cerebral cortex. Sema3F is thought to have physiological functions in the formation of neuronal circuitry and its refinement. However, functional roles of Sema3F in the brain remain to be clarified. Here, we examined behavioral effects of Sema3F deficiency through a comprehensive behavioral test battery inSema3F knockout (KO) male mice to understand the possible functions ofSema3F in the brain. Results MaleSema3F KO and wild-type (WT) control mice were subjected to a battery of behavioral tests, including neurological screen, rotarod, hot plate, prepulse inhibition, light/dark transition, open field, elevated plus maze, social interaction, Porsolt forced swim, tail suspension, Barnes maze, and fear conditioning tests. In the open field test, Sema3F KO mice traveled shorter distance and spent less time in the center of the field than WT controls during the early testing period. In the light/dark transition test, Sema3F KO mice also exhibited decreased distance traveled, fewer number of transitions, and longer latency to enter the light chamber compared with WT mice. In addition, Sema3F KO mice traveled shorter distance than WT mice in the elevated plus maze test, although there were no differences between genotypes in open arm entries and time spent in open arms. Similarly, Sema3F KO mice showed decreased distance traveled in the social interaction test.Sema3F KO mice displayed reduced immobility in the Porsolt forced swim test whereas there was no difference in immobility between genotypes in the tail suspension test. In the fear conditioning test, Sema3F KO mice exhibited increased freezing behavior when exposed to a conditioning context and an altered context in absence of a conditioned stimulus. In the tests for assessing motor function, pain sensitivity, startle response to an acoustic stimulus, sensorimotor gating, or spatial reference memory, there were no significant behavioral differences betweenSema3F KO and WT mice. Conclusions These results suggest that Sema3F deficiency induces decreased locomotor activity and possibly abnormal anxiety-related behaviors and also enhances contextual memory and generalized fear in mice. Thus, our findings suggest that Sema3F plays important roles in the development of neuronal circuitry underlying the regulation of some aspects of anxiety and fear responses.